LEGAL BASIS OF EDUCATION OF BLIND CHILDREN - Xusnuddinova Z. X. (Modern American Journals, 2025)
This article discusses the issues of physical development of children in the process of preschool education, the formation of motor skills and the promotion of a healthy lifestyle. The study analyzed the pedagogical significance of physical education classes, the effectiveness of health promotion through play activities, and the methodological approaches of educators. The results show the importance of a systematic approach to the development of coordination, endurance and muscle strength in children.
Keywords: Preschool education, physical education, motor skills, health promotion, pedagogical approach, play activities, physical development.